A Gaussian approach for analytical subthreshold current model of cylindrical nanowire FET with quantum mechanical effects. (July 2016) - Sharma, Sanjeev Kumar; Raj, Balwinder; Khosla, Mamta
Abstract: This paper proposes an analytical subthreshold current model for undoped/lightly doped Cylindrical Nanowire FETs (CGNWFETS) including quantum effects. The model is derived from direct use of Gauss's law, Drift Diffusion Approach (DDA) and effective Band Gap Widening (BGW). The Quantum Mechanical Effects (QMEs) are included in the model by taking the effects of BGW, which reduces the electron density in the subthreshold regime and reduces the subthreshold current consequently. The model explicitly shows how the oxide thickness, gate workfunction, and silicon thickness have an effect on the subthreshold current. The results obtained using proposed model is verified by comparison through SILVACO Atlas TCAD simulation; quite good agreement has been observed between model and numerical simulations results.